An analysis of spatial designs produced through mid-journey in relation to creativity standards - Müezzinoğlu, Menşure Kübra; Akan, Serpil; Dilek, Halil Yasin; Güçlü, Yelda (My University, 2023)
The purpose of this study is to comprehend how the artistic spaces developed by designer Hassan Ragab using Midjourney, one of the artificial intelligence technologies whose significance is growing every day, fit into the intersection of architecture and art. Using the random sampling method, six space modellings with three distinct forms and functions were selected for the study from the artistic spaces made by Hassan Ragab via Midjourney. People who have received or are undergoing design training were surveyed to analyze their perception of creative design principles in selected works. A total of 200 participants from two distinct design sub-professional groups were subjected to the research. According to the study, artificial intelligence offers a way for people without artistic ability to access art. Midjourney is an AI research lab with its own program and online platform that generates artwork from provided text. By using Midjourney, architectural designs can be turned into artistic works. Experts have found that most spatial designers have yet to try Midjourney and that the program has a significant impact on creative design principles like fluency, flexibility, elaboration, originality and freedom.
Keywords: Artificial intelligence; architecture; art-based research; midjourney; Hassan Ragab